Sponsorship Scale Development: A Study of a National Sports Event in New Zealand - Ashill, Nicholas; Davies, John; Joe, Anthony (School of Management Working Papers, 2000)
Despite the growing interest in sponsorship in the marketing literature, there have been few documented research efforts devoted to understanding the value or effect of sponsorship or evaluating the results for a sponsorship effort. As a step towards better understanding the effects of sponsorship on consumers, Lee et al (1997) developed and empirically tested scales to measure consumer attitudes towards sponsorship of global sports events. This paper presents the findings of a study that replicates the work of Lee et al (1997) on the measurement of consumer attitudinal constructs towards sponsorship. In particular, the study focuses on evaluating the psychometric properties of three sponsorship constructs in the context of an annual national sporting event in New Zealand. Using a mail questionnaire, 370 respondents were surveyed for their attitudes towards sponsorship of the National Provincial Rugby Championship (NPC). The results of the study demonstrate reliable and valid scales for three consumer attitudinal constructs towards sponsorship, and widen the scope of application for these scales as a research tool.